Evaluating the effectiveness of technological pedagogical content knowledge-based training program in enhancing pre-service teachers’ perceptions of technological pedagogical content knowledge - Diamah, Aodah; Rahmawati, Yuli; Paristiowati, Maria; Fitriani, Ella; Irwanto, Irwanto; Dobson, Stephen; Sevilla, Doyet (Frontiers in Education, 2022)
In this study, we sought to investigate the effect of a 2-week Technological Pedagogical Content Knowledge (TPACK)-based training program on how the pre-service teachers’ TPACK was perceived. To achieve the goal, we used four TPACK activities; Explore-Engage-Reflection-Transformation. The study employed mixed methods with a TPACK questionnaire and open questions. Increased self-efficacy perceptions of TPACK was evaluated using a one-group pre-post-post research design. The sample was 30 pre-service teachers (5 male; 25 female) at a public university in Indonesia. Paired t-test was used to examine the significant difference between pretest and posttest scores and Cohen’s d was calculated to check the strength of the effect size. As a result, the paired t-test showed that the posttest scores were significantly higher than the pretest scores for all TPACK dimensions with large effect sizes. In addition, qualitative data from students’ reflections were analyzed. It found that pre-service teachers understand the role of technology integration in the TPACK framework for creating meaningful learning experiences. Participants reflected on the role as assessment for, and as learning. Professional learning from the New Zealand education system was introduced within a holistic framework to stimulate students to be creative future-directed teachers and agents of change. This indicates that the present training program increased the pre-service teachers’ perceptions of TPACK at the end of the training. We suggest that TPACK training programs that facilitate how pre-service teachers integrate technology, content, and pedagogy to create effective technology-enriched learning environments in their subjects should be included in teacher education programs.